MENINGKATKAN HASIL BELAJAR SISWA KELAS V DENGAN PENGGUNAAN METODE DEMONSTRASI BERBANTUAN ALAT PERAGA PADA MATERI IPAS SISTEM PENCERNAAN MANUSIA DI SDN KEDOYA UTARA 04 - Siti Haerotun Nisa'i; Harlinda Syofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education aims to achieve the highest levels of intellectual, emotional, social, and physical achievement. This type of science subject includes a variety of subjects that study various natural and man-made phenomena. The study of natural sciences is usually divided into several subfields, including physics, chemistry, and biology. Classroom action research aims to identify learning process problems, plan appropriate corrective actions, implement these actions, and analyze the results. Classroom learning combines students' cognitive, emotional and psychomotor aspects. Teachers must be able to assess these three dimensions of learning outcomes objectively, because the personality of each student is different from these three dimensions. The demonstration learning method is a teacher's teaching method that provides examples or direct demonstrations of how a concept or skill should be implemented. According to data analysis, learning outcomes in science learning increased throughout Cycle I and then Cycle II. From the I cycle, the I meeting was 52%, the student completion rate increased by 13% in Cycle I to 65% at the second meeting. In Cycle II, the completion rate resulted in a 71% increase over meeting I 22,5% and at meeting II it was 93,5%. In Cycles I and II, the completion rates were 80,5% and 96,5% respectively, which was an increase of 16% from the average of the previous year's cycle.